2015
DOI: 10.3758/s13414-015-0967-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Form Integration: Sequentially presented inducers can lead to representations of stationary and rigidly rotating objects

Abstract: Objects in the world are often occluded and in motion. The visible fragments of such objects are revealed at different times and locations in space. To form coherent representations of the surfaces of these objects, the visual system must integrate local form information over space and time. We introduce a new illusion in which a rigidly rotating square is perceived on the basis of sequentially presented Pacman inducers. The illusion highlights two fundamental processes that allow us to perceive objects whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…However, because we are mobile beings and objects around us are often in motion among other objects, the locations and times at which surface fragments become visible to us is typically in flux. Behavioral research has demonstrated that perceptual representations of such objects, whether they are stationary (Kojo, Liinasuo, & Rovamo, 1993), translating (Kellman & Shipley, 1991), or rigidly rotating (McCarthy, Strother, & Caplovitz, Under Review), can be formed on the basis of the integration of local form information across space and time. Despite the importance of such spatiotemporal integration processes, relatively little is known about the neural circuitry that supports them.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, because we are mobile beings and objects around us are often in motion among other objects, the locations and times at which surface fragments become visible to us is typically in flux. Behavioral research has demonstrated that perceptual representations of such objects, whether they are stationary (Kojo, Liinasuo, & Rovamo, 1993), translating (Kellman & Shipley, 1991), or rigidly rotating (McCarthy, Strother, & Caplovitz, Under Review), can be formed on the basis of the integration of local form information across space and time. Despite the importance of such spatiotemporal integration processes, relatively little is known about the neural circuitry that supports them.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the visual system must maintain local form representations that persist when the items are no longer visible, so that they can be integrated with subsequently visible sources of information—STFI (Kojo et al, 1993; McCarthy et al, Under Review). While the mechanisms underlying spatial form integration, including processes such as modal and amodal completion, are relatively well understood (De Weerd, Desimone, & Ungerleider, 1996; Mendola, Dale, Fischl, Liu, & Tootell, 1999; Merigan, 1996; Murray et al, 2002; Pastor-Bernier, Tremblay, & Cisek, 2012; Pasupathy & Connor, 1999; Peterhans & von der Heydt, 1989; Peterhans, Von der Heydt, & Baumgartner, 1986; von der Heydt & Peterhans, 1989; von der Heydt, Peterhans, & Baumgartner, 1984), many questions about the neural processes that support STFI remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations